A Model-Driven Approach to Generate Context-Aware Applications - Duarte, Paulo A. de S.; Barreto, Felipe Mota; Gomes, Francisco Anderson de Almada; Carvalho, Windson Viana de; Trinta, Fernando Antonio Mota (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2014: Proceedings of the 20th Brazilian Symposium on Multimedia and the Web, 2014)
With the advances in mobile devices and ubiquitous computing, mobile and context-aware applications is becoming increasingly emerging. However, the development process of these applications still faces some challenges (e.g, heterogeneity of devices, complexity of the sensors access code, etc). The adoption of middleware platforms for context-aware systems is a well-known solution used to overcome such problems. An example of middleware developed for this purpose is LoCCAM, which allows adaptive acquisition of contextual information on Android based devices. But LoCCAM still presents issues concerning middleware configuration of contextual information. One approach to mitigate these existing problems is the usage of MDE (Model-Driven Engineering) paradigm. This paper shows a Visual Domain-Specific Language for modeling contextual information that is used in the development of applications using the LoCCAM. This language aims at generating skeletons of Android projects. These projects are properly configured for the use of middleware, including a transparent access to the contextual information. The main benefit of our solution it to provide a better abstraction to software developers concerning the configuration of LoCCAM middleware.